Red and White Cooperative: Challenges and Opportunities for Implementation in Manggarai Regency - Vianney, Yohanes Mario; Larum, Kordianus (West Science Interdisciplinary Studies, 2025)
Presidential Instruction of the Republic of Indonesia Number 9 of 2025 launched the national program "Red and White Cooperatives" as an effort to accelerate community-based economic development in villages. This study analyzes the challenges and opportunities for implementing the program in Manggarai Regency, East Nusa Tenggara. The method used is a descriptive-qualitative approach with data collection techniques through literature studies, documentation, and semi-structured interviews with cooperative actors and stakeholders at the local level. This study highlights local socio-cultural, geographical, and economic conditions as well as institutional readiness to support village cooperatives. It was found that this program is promising as a solution to the people's economy, but faces obstacles in terms of cooperative literacy, infrastructure, and access to capital. The output of this study is a recommendation for a cooperative implementation strategy based on local wisdom that can be applied in areas with similar characteristics.